2017
DOI: 10.1186/s12906-017-1786-0
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone (TQ) inhibits the replication of intracellular Mycobacterium tuberculosis in macrophages and modulates nitric oxide production

Abstract: BackgroundHuman tuberculosis, which is caused by the pathogen Mycobacterium tuberculosis, remains a major public health concern. Increasing drug resistance poses a threat of disease resurgence and continues to cause considerable mortality worldwide, which necessitates the development of new drugs with improved efficacy. Thymoquinone (TQ), an essential compound of Nigella sativa, was previously reported as an active anti-tuberculosis agent.MethodsIn this study, the effects of TQ on intracellular mycobacterial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…In case of Mycobacterium tuberculosis , the increasing drug resistance is a current threat to public health. Thq inhibited the replication of the extensively drug‐resistant M. tuberculosis inside of macrophages, and Thq inhibited the production of nitric oxide induced by M. tuberculosis (Mahmud et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In case of Mycobacterium tuberculosis , the increasing drug resistance is a current threat to public health. Thq inhibited the replication of the extensively drug‐resistant M. tuberculosis inside of macrophages, and Thq inhibited the production of nitric oxide induced by M. tuberculosis (Mahmud et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a major public health concern . Despite advances in the effective treatment of TB in recent years, the number of annual deaths remains almost unchanged and it is estimated that TB results in the death of about 1.5 million individuals annually, making it the most prevalent bacterial infection.…”
Section: Introductionmentioning
confidence: 99%
“…In human monocytes, the anti-inflammatory effects observed by the treatment with NS are not reported in the literature so far. Some studies showed that TQ alone suppressed the expression of IL-6 from Mycobacterium tuberculosis infected human monocyte THP-1 cells ( Mahmud et al, 2017 ). Furthermore, TQ inhibited the production of IL-6 in LPS-activated murine macrophage-like RAW264.7 cells ( Hossen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%